Sinergisitas efek sitotoksik kombinasi arekolin dan doxorubicin pada sel kanker serviks HeLa - Astrid Ayu Maruti; Rahmi Khamsita; Suven .; Dyaningtyas Dewi Putri; Edy Meiyanto (Indonesian Journal of Pharmacy, 2011)
Arecoline, the main alcaloid of Areca cathecuL has been proven to posses cytotoxic  activity  against  various  cancer  cell  lines.  The  research  conducted  to examine  the  cytotoxic  activity  of  arecoline  alone  and  its  combination  with doxorubicin  against  HeLa  cervical  cancer  cell  line.  Single treatment  of arecoline  in  various  concentration  on  HeLa  cancer  cell  were  done  followed  by the  combinational  treatment  with  doxorubicin.  The  cell  viability  as  the parameter  of  cytotoxicity  was  measured  using  MTT  (3-(4,5-dimetiltiazol-2-il)-2,5-difeniltetrazolium  bromide)  assay.  The  apoptotic  effect  was  examined  by double staining assay using etidium bromide – acridin orange. Arecoline did not show  potent  cytotoxicity  effect  against  HeLa  since  the  value  of  IC50 is  462µM. The  combinational  treatment  of  arecoline  and  doxorubicin  showed  synergicity with  the  optimum  CI  value  is  0,48  given  by  the  treatment  of  30mM  arecoline combined with 125 nM doxorubicin. The result of this study shows that arecoline has potential  to  be proposed  as  co-chemotherapeutic  agent for  cervical cancer. However, further study on its molecular mechanism needs to be conducted.Key words: arecoline, synergicity, doxorubicin, MTT assay, HeLa cell line